Origin and early evolution of Ceropegieae (Apocynaceae-Asclepiadoideae). Issue 2 (4th March 2017) - Meve, Ulrich; Heiduk, Annemarie; Liede-schumann, Sigrid
Abstract : The first-branching lineages of the tribe Ceropegieae, Anisotominae, Leptadeniinae, and Heterostemminae, are the focus of the present study. In the ingroup we molecularly analysed 34 samples from southern and (north)eastern Africa and Asia for the nuclear internal transcribed spacer (ITS) region, and five plastid markers ( trn T-L, trnL-F and trn H -psb A intergenic spacers, trn L, and rps 16 introns). Maximum Parsimony and Bayesian analyses were conducted for phylogenetic reconstruction and Bayesian binary MCMC (BBM) analysis as implemented in RASP for testing biogeographic inference. Sister to the well-known hyperdiverse subtribe Stapeliinae (around 700 species) are the Anisotominae, an African subtribe of c . 30 species, with the tropical Neoschumannia in sister-group position to the remaining genera, Anisotoma, Emplectanthus, Riocreuxia, and Sisyranthus . Emplectanthus is sequenced in full for the first time, and its monophyly as sister to Anisotoma is documented. As in Sisyranthus, new sequences in Riocreuxia, especially in Riocreuxia torulosa s.l., reveal very low genetic variation pointing to an actively radiating and speciating group, possibly in adaptation to pollinator pressure. Molecular and morphological data necessitate the transfer of Brachystelma natalense to Anisotoma, and the new combination Anisotoma natalensis is proposed. Leptadeniinae are sister to the Stapeliinae–Anisotominae clade. The position of the strictly Asian, rheophytic Pentasachme could be resolved as sister to the remaining genera of Leptadeniinae, Conomitra, Leptadenia, and Orthanthera . The position of the S Asian/Australasian wet forest lianas of the genus Heterostemma as sister to the remaining Ceropegieae is confirmed, indicating a humid Asian origin for this tribe known for its arid-adapted African succulents.